Acute thrombocytopenia induced by trastuzumab due to complement reaction: A case report - Chen, Guoping; Ou, Jianghua; Liu, Jun; Liao, Haoran; Ding, Linwei; Fan, Pingming; Du, Guankui (Frontiers in Medicine, 2022)
Background The usual treatment option for HER2 breast cancer is targeted therapy with trastuzumab. The common adverse effects of trastuzumab treatment are thrombocytopenia, however, acute thrombocytopenia is rare and its mechanism is still largely unknown. Case presentation We reported a patient who presented with acute thrombocytopenia on two consecutive occasions, and the predisposing factor was identified on the second occasion because of trastuzumab-only treatment. Routine blood results showed a dramatic increase in white blood cell count and neutrophil count after both trastuzumab treatments. Moreover, the complement reaction results suggested that the dramatic thrombocytopenia was probably due to platelet destruction after complement activation. Conclusion This case suggests that it would be useful to perform a platelet complement reaction test before trastuzumab treatment in patients with HER2 breast cancer.